2021
DOI: 10.1111/1756-185x.14247
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Takayasu’s arteritis has a high risk of hypertension‐related fetomaternal complications: A retrospective study of a Turkish cohort

Abstract: Background This study aimed to examine fetomaternal outcomes in pregnant women in a large Turkish Takayasu arteritis (TAK) cohort and to evaluate the effects of pregnancy on the disease in those patients. Methods This is a cohort study involving 296 pregnancies of 112 TAK patients from 8 tertiary rheumatology centers in Turkey. Pregnancies were divided into 2 groups as pre‐d (before disease onset) and post‐d (after disease onset). In addition, post‐d pregnancies were further divided into 2 subgroups according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…Our study found only six TA patients (6.8%) who developed preeclampsia and one patient eclampsia in striking contrast to the literature report of up to 75.9% in the preeclampsia/eclampsia rate [ 6 , 20 22 ]. The low incidence of eclampsia/preeclampsia in our study may be due to the effective management of hypertension and TA disease before and following pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our study found only six TA patients (6.8%) who developed preeclampsia and one patient eclampsia in striking contrast to the literature report of up to 75.9% in the preeclampsia/eclampsia rate [ 6 , 20 22 ]. The low incidence of eclampsia/preeclampsia in our study may be due to the effective management of hypertension and TA disease before and following pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, our results have shown that the main complications associated with TA are new-onset or worsening hypertension for mothers and preeclampsia, abortion, low birth weight prematurity, and in utero death for fetuses. Inconsistencies within the literature exist regarding the report of maternal complications and fetal outcomes associated with TA in distinct studies [ 6 , 19 ]. Hypertension is the most common maternal complication in women with TA, with incidence rates ranging from 5.3% to 100% [ 6 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, advanced maternal age or prolonged disease duration did not predispose to obstetric complications 8 . Gönenli et al, also reported that maternal age did not oppose as risk factor for poor pregnancy outcomes, in contrast to vascular damage, and recent diagnosis, commonly associated with uncontrolled inflammation and high disease activity 40 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, advanced maternal age or prolonged disease duration did not predispose to obstetric complications 8 . Gönenli et al, also reported that maternal age did not oppose as risk factor for poor pregnancy outcomes, in contrast to vascular damage, and recent diagnosis, commonly associated with uncontrolled inflammation and high disease activity 40 . www.nature.com/scientificreports/ New onset and/or aggravation of hypertension appear to be the main maternal complications in our analysis, which concurs with previous studies 8 .…”
Section: Discussionmentioning
confidence: 99%